Comparative proteomic analysis of bronchoalveolar lavage of familial and sporadic cases of idiopathic pulmonary fibrosis. (15th April 2016) - Carleo, A; Bargagli, E; Landi, C; Bennett, D; Bianchi, L; Gagliardi, A; Carnemolla, C; Perari, M G; Cillis, G; Armini, A; Bini, L; Rottoli, P
Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease characterized by progressive deterioration of the alveolar integrity. Among IPF identified phenotypes, that of familial (f-)IPF is usually associated with several gene mutations which are seldom observed in sporadic (s-)IPF. This study aimed at investigating the molecular patterns and variability in f-IPF and s-IPF patients through a differential proteomic analysis. Protein patterns of bronchoalveolar lavage fluid (BALF) samples from 10 familial and 17 sporadic IPF patients were compared using 2D electrophoresis and mass spectrometry. Principal component analysis (PCA) was applied to proteomic data and an enrichment analysis was also performed to characterize specific pathogenic mechanisms and to identify potential biomarkers. BALF samples from f-IPF showed 87 protein spots differentially expressed than those from s-IPF samples; once identified, these spots revealed 22 unique proteins. The functional analysis showed that the endothelial reticulum stress probably plays a central pathogenetic role in f-IPF with an up-regulation of proteins involved in wounding and immune responses, coagulation system, and ion homeostasis. Up-regulated proteins in the s-IPF group were those involved in the oxidative stress response. PCA analysis of differentially expressed proteins clearly distinguished f-IPF from s-IPF patients, and in agreement with radiological and histological patterns, pointed out a higher heterogeneity in f-IPF than s-IPF samples. The 'Slit/Robo signaling', 'clathrin-coated vesicle' and 'cytoskeleton remodelling', were extrapolated by 'pathways analysis' and the results of 'diseases (by biomarkers)' highlighted a 'connective tissue and autoimmune disease', two aspects of increasing interest in IPF.